Ultrasonographic Assessment of The Fetal Foot Length for Gestational Age Estimation - Yüksel, Kutlugül; Günyeli, İlker and Doğanay, Melike and Uğur, Mustafa and Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To describe the relationships between gestational age and ultrasonographic measurement of fetal f oot length. STUDY DESIGN: A total of 462 ultrasonographic measurements were performed to describe the relationship between gestational age and fetal foot length at the Zekai Tahir Burak Woman Health Education and Research Hospital. The nomogram of f etal foot length v ersus gestational age between 15-42 weeks was constructed f rom the fetuses of healthy singleton pregnancies. All patients had normal ongoing pregnancies and known last menstrual periods. RESULTS: A significant correlation was f ound between fetal f oot length and gestational age (r = 0.890, p < 0.0001). Our results suggested that f etal foot length was a reliable marker f or use in the assessment of gestational age. CONCLUSION: This parameter is particularly usef ul when other measurements do not accurately predict gestational age, for example, dysplastic limb reduction and abnormal fetal head structure.